Progressive Retinal and Optic Nerve Damage in a Mouse Model of Spontaneous Opticospinal Encephalomyelitis - Petrikowski, Laura; Reinehr, Sabrina; Haupeltshofer, Steffen; Deppe, Leonie; Graz, Florian; Kleiter, Ingo; Dick, H. Burkhard; Gold, Ralf; Faissner, Simon; Joachim, Stephanie C. (Frontiers in Immunology, 2022)
Neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein-antibody-associated disease (MOGAD) are antibody mediated CNS disorders mostly affecting the optic nerve and spinal cord with potential severe impact on the visual pathway. Here, we investigated inflammation and degeneration of the visual system in a spontaneous encephalomyelitis animal model. We used double-transgenic (2D2/Th) mice which develop a spontaneous opticospinal encephalomyelitis (OSE). Retinal morphology and its function were evaluated via spectral domain optical coherence tomography (SD-OCT) and electroretinography (ERG) in 6- and 8-week-old mice. Immunohistochemistry of retina and optic nerve and examination of the retina via qRT-PCR were performed using markers for inflammation, immune cells, and the complement pathway. OSE mice showed clinical signs of encephalomyelitis with an incidence of 75% at day 38. A progressive retinal thinning was detected in OSE mice via SD-OCT. An impairment in photoreceptor signal transmission occurred. This was accompanied by cellular infiltration and demyelination of optic nerves. The number of microglia/macrophages was increased in OSE optic nerves and retinas. Analysis of the retina revealed a reduced retinal ganglion cell number and downregulated Pou4f1 mRNA expression in OSE retinas. RT-qPCR revealed an elevation of microglia markers and the cytokines Tnfa and Tgfb. We also documented an upregulation of the complement system via the classical pathway. In summary, we describe characteristics of inflammation and degeneration of the visual system in a spontaneous encephalomyelitis model, characterized by coinciding inflammatory and degenerative mechanisms in both retina and optic nerve with involvement of the complement system.